Nociceptive Flexion Reflex Threshold is No Suitable Marker for Diagnosing Opioid-Induced Hyperalgesia - Trübenbacher L; Lindenberg N; Graf BM; Backmund M; Unglaub W; Lassen CL (Journal of Pain Research, 2024)
Luisa Trübenbacher,1 Nicole Lindenberg,1 Bernhard M Graf,1 Markus Backmund,2 Wilhelm Unglaub,3 Christoph L Lassen1 1Centre for Interdisciplinary Pain Medicine, Department of Anaesthesiology, University Hospital of Regensburg, Regensburg, 93053, Germany; 2“Praxiszentrum im Tal”, Tal 9, 80331, Ludwig-Maximilians-University, Munich, Germany; 3“medbo” District Hospital, Universitätsstraße 84, 93053, University of Regensburg, Regensburg, GermanyCorrespondence: Luisa Trübenbacher, Department for Anaesthesiology, University Hospital of Regensburg, Franz-Josef-Strauss-Allee 11, Regensburg, 93053, Germany, Tel +49 941 944-7810, Fax +49 941 944-7832, Email luisa.truebenbacher@stud.uni-regensburg.deBackground: Opioid induced hyperalgesia (OIH) describes a state of altered pain sensation due to opioid exposure. It often occurs among persons with opioid use disorder receiving substitution therapy.Methods: The purpose of this study was to find out, whether OIH diagnosis could be facilitated by an objective pain indicating marker: the Nociceptive Flexion Reflex (NFR). Forty persons with opioid use disorder, 20 of them maintained on methadone and 20 treated with buprenorphine, as well as a control group of 20 opioid-free subjects, were examined. It was aimed to find out whether and in which way these opioid agonists alter reflex threshold (NFR-T). A cold-pressor test was performed to investigate the prevalence of OIH. Furthermore, electrical stimulation and electromyography analyzation were used for NFR-T measurement. Subjective pain ratings were evaluated with a numeric rating scale.Results: Significantly increased sensitivity to cold pressor pain was found in both maintenance groups when compared to their opioid-free counterparts (p < 0.001). Neither methadone nor buprenorphine showed any effect on NFR-T. This might be explained by the reflex approaching at the wrong location in the central nervous system. Consequently, NFR-T is not a suitable marker for diagnosing OIH.Conclusion: Although methadone and buprenorphine have been proven to cause OIH, no effect on NFR-T was observed. A statistically significant effect could have been observed with a larger number of participants. Further research, with special focus on patients’ adjuvant medication, should be conducted in the future, to facilitate diagnosis of OIH and provide appropriate pain management for maintenance patients.Keywords: hyperalgesia, analgesics, opioid, substance-related disorders, methadone, buprenorphine